A Chemical Route Towards Single‐Phase Materials with Controllable Photoluminescence. (15th July 2015) - Kaur Behrh, Gaganpreet; Serier‐Brault, Hélène; Jobic, Stéphane; Gautier, Romain
Abstract A promising general approach is proposed that enables the controlled reduction of dopants to tune the photoluminescence properties of single‐phase materials. The change of oxidation state of dopants in phosphor phases leads to different emission colors that can be finely tuned. This approach was illustrated with the progressive reduction of the red phosphor SrAl2O4:Eu3+ to green phosphor SrAl2O4:Eu2+ to target yellow luminescence.